PENDIRIAN BADAN HUKUM KOPERASI DALAM UPAYA MEMBANGKITKAN PARTISIPASI MASYARAKAT GUNA PEMBERDAYAAN KELEMBAGAAN DESA TERTINGGAL - Purwaningsih, Endang; Basrowi, Basrowi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The role of establishing cooperative legal entities in generating community participation for institutional empowerment in underdeveloped villages. Legally incorporated cooperatives are believed to be able to become a driving force in optimizing local economic potential through collective business management that actively involves the community. Methods: This research was conducted in Kadubelang Village, Mekarjaya District, Pandeglang Regency, and aims to (1) raise the interests of small communities, namely underdeveloped villages, accommodate their aspirations and motivations in efforts to establish the desired legal entity, and (2) specifically describe the level of participation in empowering the institution that will be established, namely in the form of a cooperative.Results: This research shows that village cooperatives can significantly create economic opportunities, reduce poverty, and improve socio-economic conditions in underdeveloped villages. It is hoped that the results of this research can become a reference in developing policies that support strengthening village institutions and increasing community participation in inclusive and competitive village development. Keywords: Cooperatives, Participation, Empowerment, Institutions, Underdeveloped Villages